Ethnomathematical Exploration in the Geulis Group Tasikmalaya West Java - Astrid Sulistya Azahra; Detalia Noriza Munahefi; Kristina Wijayanti; Agung Prabowo (International Journal of Ethno-Sciences and Education Research, 2022)
In this study, mathematical concepts are used to explore the existence of mathematics in culture, especially in the Tasikmalaya group of geulis. By observing the current conditions, the activity of making kelom geulis is seen as a "mathematical-free" activity. It is still rare and there is still a lack of public knowledge about ethnomathematics which colors the activities of making kelom geulis as a motivation to investigate the mathematical knowledge contained in it. In addition, with the decreasing number of kelom geulis craftsmen as a result of the use of kelom geulis left by the original community producing these products. This study aims to determine and describe the ethnomathematics of the geulis group. The method used is qualitative with ethnographic methods. The subjects in this study were selected using a purposive sampling method with the research subject being a kelom geulis craftsman in the Tamansari (Gobras) area, Mulyasari, Tasikmalaya. Data collection techniques used are interviews, observation and documentation. The data analysis technique used in the research is data reduction, data presentation and drawing conclusions. Based on the results of data analysis, it can be concluded that there are mathematical concepts in the geulis group, especially in the discussion of flat shapes such as rectangles, circles and triangles. This research also produces a linear equation that relates the length of the foot to the size of the geulis group.